2014
DOI: 10.2337/db13-1612
|View full text |Cite
|
Sign up to set email alerts
|

A Maternal Gluten-Free Diet Reduces Inflammation and Diabetes Incidence in the Offspring of NOD Mice

Abstract: Early-life interventions in the intestinal environment have previously been shown to influence diabetes incidence. We therefore hypothesized that a gluten-free (GF) diet, known to decrease the incidence of type 1 diabetes, would protect against the development of diabetes when fed only during the pregnancy and lactation period. Pregnant nonobese diabetic (NOD) mice were fed a GF or standard diet until all pups were weaned to a standard diet. The early-life GF environment dramatically decreased the incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
83
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 43 publications
7
83
0
3
Order By: Relevance
“…We have previously shown that a SGF diet reduces incidence of T1D in NOD mice to 6% compared to 15% in GF [1,51]. Recently, it was shown in NOD mice that a maternal GF diet reduces diabetes incidence in the offspring [52]. Thus, our data indicate that a GF diet may prevent diabetes, by generally reducing the number of NKp46 + NK cells, cellular proliferation, and downregulating the activating receptor NKG2D on NK cells, making them less autoreactive.…”
mentioning
confidence: 48%
“…We have previously shown that a SGF diet reduces incidence of T1D in NOD mice to 6% compared to 15% in GF [1,51]. Recently, it was shown in NOD mice that a maternal GF diet reduces diabetes incidence in the offspring [52]. Thus, our data indicate that a GF diet may prevent diabetes, by generally reducing the number of NKp46 + NK cells, cellular proliferation, and downregulating the activating receptor NKG2D on NK cells, making them less autoreactive.…”
mentioning
confidence: 48%
“…Studies in mice demonstrate that a maternal glutenfree diet increases the number of Akkermansia, Proteobacteria, in the offspring's gut microbiota and reduces the incidence of diabetes and low-grade inflammation [18]. It has also been shown in humans that an "unhealthy" mother's diet during pregnancy or poor early childhood nutrition can lead to the establishment of a defective intestinal microbiota [19].…”
Section: Interventions During Pregnancymentioning
confidence: 99%
“…Other components from cow’s milk, such as casein, can alter gut permeability and potentially promote the incidence of T1D (22, 23). Food-derived gluten has also been shown to modify gut permeability and again potentially affect the development of T1D (20, 21). Interestingly, mice treated with a gluten-free diet showed modifications in gut microbiota and protection from T1D (20, 21).…”
mentioning
confidence: 99%
“…Food-derived gluten has also been shown to modify gut permeability and again potentially affect the development of T1D (20, 21). Interestingly, mice treated with a gluten-free diet showed modifications in gut microbiota and protection from T1D (20, 21). Consistently, accumulating studies showed in recent years the involvement of environment factors, particularly an association with gut microbiota, in the pathogenesis of T1D.…”
mentioning
confidence: 99%